Click start level 6 computer science for schools - Virmani, Anjana; Harisukh, Shalini (Cambridge University Press UK, 2013)
Click Start: Computer Science for Schools is an eight-level series of textbooks for students. The series has been developed keeping in mind the latest trends in the field of information and communication technology. The series is based on Windows 7 and MS Office 2007 with extensive updates on Windows 8 and MS Office 2010. The books serve as a key to understanding the latest software, programming concepts and programming languages.